2008
DOI: 10.1152/ajpheart.00046.2007
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic effects on QT-RR interval dynamics after exercise

Abstract: This study was designed to assess autonomic effects on the QT interval during recovery from exercise. Exercise is associated with an acute increased risk of sudden cardiac death. Evidence of impaired parasympathetic activity, such as low heart rate variability and heart rate recovery, and an increased QT interval are also associated with increased mortality. However, there is no clear pathophysiological link among these findings. Bicycle exercise testing was performed serially in 33 healthy volunteers (19 men;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 54 publications
3
18
2
Order By: Relevance
“…In subjects who submitted to moderate exercise testing, it was observed that a parasympathetic blockade might provide an arrhythmic effect during the post-exercise time, with a significantly increased QT interval. 20 In the present study, AAS users and non-user subjects showed a lengthening in QTc after exercise; however, the AAS group presented a higher increment in QTc interval than the control group. Furthermore, the AAS group presented increased QTd compared with the control group, with a rest value higher than 65 ms, suggesting abnormal ventricular repolarization in those AAS users.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…In subjects who submitted to moderate exercise testing, it was observed that a parasympathetic blockade might provide an arrhythmic effect during the post-exercise time, with a significantly increased QT interval. 20 In the present study, AAS users and non-user subjects showed a lengthening in QTc after exercise; however, the AAS group presented a higher increment in QTc interval than the control group. Furthermore, the AAS group presented increased QTd compared with the control group, with a rest value higher than 65 ms, suggesting abnormal ventricular repolarization in those AAS users.…”
Section: Discussioncontrasting
confidence: 49%
“…26 Nevertheless, a measurement of QT dispersion > 90 ms identified patients at increased risk of cardiac death. 20 Salles et al 13 showed for patients with Chagas' disease, that a maximal dispersion of the QT interval greater than 65 ms and a maximum corrected QT interval longer that 465 ms are independent predictors of sudden death. In the present study, the AAS group had a rest QTd > 65 ms and although the maximum QTc was below 465 ms at rest, it increased to a value > 465 ms at the postexercise recovery time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(12) Briefly, participants had normal physical examinations, ECGs, hematocrits, and serum electrolytes, were without cardiac complaints, and were not taking cardioactive medications. The study was approved by the Northwestern University Institutional Review Board and all participants provided written, informed consent.…”
Section: Methodsmentioning
confidence: 99%